Analysing Students' Perception of Web-Based Learning with Quizziz Application in Reading Comprehension at SMP Negeri 3 Sungguminasa - Bakhtiar, Khalid Bilal; Iskandar, Iskandar; Sunra, La (International Journal of Contemporary Studies in Education, 2024)
Learning motivation is one of the determining factors in achieving learning objectives. From learning motivation, students have the desire to follow learning continuously. Therefore, a teacher must be able to increase student motivation in learning and there are many ways that teachers can use to increase student motivation and one way to increase student motivation is to use media that is fun and easy for students to use. Quizizz is one of the learning applications used by SMP Negeri 3 Suangguminasa. So, researchers conducted research on students' perceptions of using the Quizizz application. The data collection techniques used by researchers are questionnaires and documentation. The results of this study show that the perception of VIII B students at SMP Negeri 3 Sungguminasa is motivated by the application of learning using the quizizz application. The application of the quizizz application makes students happy to use it and feels easy and easy to use, the results are very good because it can help in the process of learning English because it has many useful features that indirectly make students excited.